Penerapan Sistem Penjadwalan Dengan Metode SPT (Short Processing Time) Dan EDD (Earliest Due Date) Dalam Mengefisiekan Biaya Operasional Dan Sumber Daya Pada Perusahaan PT. Mathar Telekomunikasi Indonesia - Wasito, Wasito; Budiman, Dewinda Almira Noor; Juniarti, Atty Tri; Sarman, Rohmat (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2024)
This research aims to implement a more efficient scheduling system using the SPT (Short Processing Time) and EDD (Earliest Due Date) methods at PT. Mathar Telekomunikasi Indonesia. Currently, the company still uses the FCFS (First Come First Served) method, where work is prioritized based on the order of arrival without considering the due date. As a result, delays in scheduling occur, leading to increased operational costs and less efficient use of resources.To address this issue, the researcher proposes the implementation of the SPT method, where jobs with shorter production times are completed first, and the EDD method, where jobs with earlier due dates are prioritized. It is expected that the implementation of these two methods will streamline operational costs and resources. Scheduling that occurs in the company PT. Mathar Telekomunikasi Indonesia is still experiencing delays due to constraints that occur in the scheduling process, problems that occur include damage to machines, resources that are still less effective and efficient. For now, the company still uses the FCFS (First Come First Served) method, in which work is prioritized regardless of the due date. Delays in scheduling have an effect on swollen operational costs and less efficient resources at work. The researcher proposes that companies use the priority rule method, namely SPT (Short Processing Time) where the shorter production time is done first, then the second method, namely the EDD (Earliest Due Date) method, the production process with a faster maturity is prioritized by the researcher. hopes to streamline operational costs and resources.The results of the research that has been carried out show that the average completion time for the SPT and EDD methods is a difference of 3 days where the SPT method is greater than the EDD, the utility results for both methods are 0%, the average amount of work is 0 where the EDD method is greater from the SPT method, the result of the delay from the two methods is 2 days. The operational cost that is a problem is the cost of fines on projects the company is working on must spend Rp. 134,516,831. The problematic resources in the company are work discipline, work productivity, work competence, and leadership